A Chandra survey of milky way globular clusters – III. Searching for X-ray signature of intermediate-mass black holes. Issue 2 (22nd August 2022) - Su, Zhao; Li, Zhiyuan; Hou, Meicun; Zhang, Mengfei; Cheng, Zhongqun
ABSTRACT: Globular clusters (GCs) are thought to harbor the long-sought population of intermediate-mass black holes (IMBHs). We present a systematic search for a putative IMBH in 81 Milky Way GCs, based on archival Chandra X-ray observations. We find in only six GCs a significant X-ray source positionally coincident with the cluster centre, which have 0.5–8 keV luminosities between ∼1 × 10 30 erg s −1 and ∼4 × 10 33 erg s −1 . However, the spectral and temporal properties of these six sources can also be explained in terms of binary stars. The remaining 75 GCs do not have a detectable central source, most with 3σ upper limits ranging between 10 29–32 erg s −1 over 0.5–8 keV, which are significantly lower than predicted for canonical Bondi accretion. To help understand the feeble X-ray signature, we perform hydrodynamic simulations of stellar wind accretion on to a 1000 M⊙ IMBH from the most-bound orbiting star, for stellar wind properties consistent with either a main-sequence (MS) star or an asymptotic giant branch (AGB) star. We find that the synthetic X-ray luminosity for the MS case (10^19 erg s^-1 ) is far below the current X-ray limits. The predicted X-ray luminosity for the AGB case (10^34 erg s^-1 ), on the other hand, is compatible with the detected central X-ray sources, in particular the ones in Terzan 5 and NGC 6652. However, the probability of having an AGB star as the most-bound star around the putative IMBH is very low. Our study strongly suggests that it is very challenging to detect the accretion-induced X-ray emission from IMBHs, even if they were prevalent in present-day GCs.